2013
DOI: 10.4028/www.scientific.net/amr.652-654.1700
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Photocatalytic Properties of Iron Doped Titania Photocatalyst by Degradation of Methylene Blue Using Fluorescent Light Source

Abstract: Transition metal ion-doped titanium dioxide (TiO2) powders were prepared by mechanochemical milling. Photocatalytic properties of the prepared semiconductor were evaluated using photodegradation of methylene blue under UV and visible light. Dye bleaching was observed spectrophotometrically. Color removal was reached after 120 min. The effect of varying concentration of organic dye, amount of TiO2 photocatalyst, particle size, pH, and stirring rate was observed on the efficiency of reaction. The maximum photoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The selection of the type of semiconductor is based on its ability to convert the vat dyes into nontoxic products [ 44 , 90 , 177 , 178 ]. Additionally, the use of mesoporous materials, like zeolite as a support for these series of semiconductors, has recently become the focus of intensive research on vat dye photodecolorization, due to the fact that the semiconductor support influences the photocatalytic efficiency through structural features, and the interaction between the vat dyes leads to the enhancement of contact between the surface, and irradiation likewise decreases with the amount of semiconductor required [ 179 ]. Thus, there are some studies focused on the importance of semiconductor supported zeolite for vat dye photodegradation, including Co-ZSM-5, TiO 2 -HZSM-5, Fe-exchange zeolite, and CuO-X zeolite [ 180 , 181 ].…”
Section: Photocatalytic Decolorization Of Synthetic Dyesmentioning
confidence: 99%
“…The selection of the type of semiconductor is based on its ability to convert the vat dyes into nontoxic products [ 44 , 90 , 177 , 178 ]. Additionally, the use of mesoporous materials, like zeolite as a support for these series of semiconductors, has recently become the focus of intensive research on vat dye photodecolorization, due to the fact that the semiconductor support influences the photocatalytic efficiency through structural features, and the interaction between the vat dyes leads to the enhancement of contact between the surface, and irradiation likewise decreases with the amount of semiconductor required [ 179 ]. Thus, there are some studies focused on the importance of semiconductor supported zeolite for vat dye photodegradation, including Co-ZSM-5, TiO 2 -HZSM-5, Fe-exchange zeolite, and CuO-X zeolite [ 180 , 181 ].…”
Section: Photocatalytic Decolorization Of Synthetic Dyesmentioning
confidence: 99%
“…Many researchers report successful doping Titanium dioxide by metal cations and non metal anions. Fe doped TiO 2 fabricated by mechanochemical milling performed very good photocatalytic properties for photodegradation of Methylene Blue [1]. For better understanding of doping mechanism X-Ray Photoelectron spectroscopy was used.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to lower surface are. In our previous paper we reported that amount of TiO 2 plays crucial role in photocatalytic reaction [11]. Fig.…”
Section: Applied Science and Precision Engineering Innovationmentioning
confidence: 91%
“…photoconversion to formic acid using Fe doped TiO 2 photocatalyst. In our previous [11][12] papers we reported about excellent photocatalytic activity of Fe doped TiO 2 prepared by mechanochemical milling for photodegradation of organic dyes. Due to these properties we decided to utilize it for photoconversion of CO 2 and H 2 O to hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%